2018
DOI: 10.1016/j.gore.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Tumor lysis syndrome associated with docetaxel and carboplatin in a case with recurrent endometrial cancer

Abstract: Tumor lysis syndrome (TLS) is an oncological life-threatening complication characterized by hyperuricemia, hyperphosphatemia, and hyperkalemia, which can lead to acute renal failure, cardiac arrhythmias, cardiac arrest and seizures. Although TLS is a rare complication in patients with non-hematological malignancy, the mortality rate of TLS in solid tumors is higher than that in hematological malignancies. Acute renal injury is the most common cause of mortality associated with TLS in solid tumors. We report a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Ito et al reported a patient with TLS following docetaxel and carboplatin treatment for recurrent endometrial cancer. This patient developed classic laboratory abnormalities for TLS, AKI, in conjunction with sudden onset chest pain, hypoxia, and respiratory distress 19 hours after initiation of chemotherapy, and the autopsy, thereafter, showed pulmonary tumor embolism [28].…”
Section: Human Autopsy Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Ito et al reported a patient with TLS following docetaxel and carboplatin treatment for recurrent endometrial cancer. This patient developed classic laboratory abnormalities for TLS, AKI, in conjunction with sudden onset chest pain, hypoxia, and respiratory distress 19 hours after initiation of chemotherapy, and the autopsy, thereafter, showed pulmonary tumor embolism [28].…”
Section: Human Autopsy Studiesmentioning
confidence: 91%
“…Several documented case reports of TLS in humans appear to echo animal model findings, as microemboli appear to play a direct role in widespread tissue damage [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The demographics, clinicopathologic features, autopsy findings, and outcomes are summarized in Table 2.…”
Section: Human Autopsy Studiesmentioning
confidence: 99%
“…Studies in mice found disseminated microemboli from lysed tumor cells during the histopathological postmortem examination; these result in widespread tissue damage, multiorgan failure, and death [34][35]. Those findings closely mimic the human autopsy findings of disseminated tumor embolism leading to massive tissue organ necrosis and death [36][37]. Furthermore, concurrent disseminated intravascular coagulation was proposed as a probable mechanism that could synergistically lead to increased mortality in patients with TLS through common pathogenesis and pro-inflammatory cytokine-mediated processes [13][14].…”
Section: Discussionmentioning
confidence: 61%
“…Autopsy of this patient revealed disseminated microthrombi in the portal system, but more importantly, massive necrosis of normal hepatocytes was noted alongside melanoma cell death within the liver [ 16 ]. In another study, Ito et al reported a case of recurrent endometrial cancer presenting with TLS about 19 hours after initiation of docetaxel and carboplatin therapy [ 17 ]. In addition to hyperuricemia, hyperkalemia, and hypocalcemia, the patient showed symptoms of chest pain, tachypnea, and oliguria.…”
Section: Discussionmentioning
confidence: 99%
“…Although hyperkalemia and metabolic acidosis were managed successfully, right-sided heart failure ultimately led to her death 54 hours after chemotherapy. Autopsy confirmed disseminated microemboli in what was otherwise a normal lung [ 17 ].…”
Section: Discussionmentioning
confidence: 99%